Compressive Strength of Micro Steel Fiber Concrete - Afrizal, Mohd Azim; Shahidan, Shahiron (Recent Trends in Civil Engineering and Built Environment, 2022)
This study to investigate the compressive strength of micro steel fibre concrete (MSFC). To this end, the different micro steel fibre content (0.5%, 0.75%, 1.0% and 1.25%) were used. The objective of this study is to determine the compressive strength behaviour in concrete and the optimum micro steel fibre to be used. The slump test and compression test were conducted. Generally, as the percentage of MSF increase, the compressive strength will increase meanwhile reduce the workability of concrete. In conclusion, the present of MSF in concrete can increase the value for compressive strength for MSFC.